ETNOMATEMATIKA NAGEKEO PADA KAIN TENUN OBA AGI OBA PETE DALAM PEMBELAJARAN MATEMATIKA - Priska Ermelinda Noa; Melkhior Wewe (Lembaga PKBM Tunas Harapan Varoso, 2024)
Directorate of Culture is closely related to science, one of the Directorates in the field of mathematics. Ethnomatics is the part and science of Dis knowledge related to mathematics that is applied to well-identified cultural community groups. Ka Nagekeo culture has many symbols that are related to Etr mathematics and have meanings related to Na school mathematics lessons. The purpose of this writing is to study symbols. - Ika Nagekeo cultural symbols and various shapes and models related to mathematics learning, such as Ma, Oba Aqı Oba Pete woven cloth. The method used in writing the literature review is using descriptive analysis. The results of the study show that the Nagekeo traditional symbols represent mathematics in the geometric aspect , such as rectangular shapes, curved side shapes, and simple curves. This study was used by educators and students in learning mathematics based on local Nagekeo culture and loving the cultural traditions of the local area. Based on the results of observations and documentation, it can be concluded that the oba aqı and oba pete woven fabrics are ancestral, cultural and local community motifs found on the fabrics. oba agi oba pete ikat weaving has rectangular hexagon (broken pinng) and rhombus (rurf) motifs. The tradition of buying and selling ikat woven fabrics, oba açı and oba pete, people use money or exchange woven fabrics for pets, such as buying and selling transactions carried out by village communities. Nagerawe at the Boawae traditional market which uses the anmatics model in the operations of addition, subtraction, multiplication and division. This shows that the connection between mathematics and oba agi and oba pete woven fabrics is 100% valid.